Carbon nanotubes/cellulose composite aerogels with controllable microstructure for electromagnetic interference shielding. Issue 8 (23rd December 2022) - Li, Ying; Shi, Qin; Peng, Longgui; Chang, Mengjie; Zhou, Fang; Gong, Changdan; Wu, Yi; Zhang, Liangqing
Abstract: In this work, isotropic cellulose aerogels with microstructure from three‐dimensional (3D) sheet‐networks to 3D nanofibrous networks are obtained by adjusting the tertiary butanol content and using the homogenous freezing method. When changing the freezing method to unidirectional freezing, the microstructure of cellulose aerogels transforms from isotropic to oriented fibrous network structure. The mechanical performance of cellulose aerogels presents microstructure‐dependent behavior. Furthermore, serviceable conductivity and electromagnetic interference (EMI) shielding performance are imparted to cellulose aerogels by uniformly dispersing carbon nanotubes (CNTs) into cellulose matrixes. With the same CNT content (10 wt%), oriented CNTs/cellulose composite aerogels show higher EMI shielding efficiency (EMI SE) than that of isotropic composite aerogels. One possible reason is that oriented composite aerogels can reflect and absorb the electromagnetic waves much more times along the freezing direction. The specific SE (716 dB cm 3 g −1 ) of oriented composite aerogel is higher than that of isotropic composite aerogel (539 dB cm 3 g −1 ), which is the reason that oriented composite aerogel has lower density and higher SE. These advantages of lightweight, controllable microstructure, adjustable EMI shielding performance give CNTs/cellulose composite aerogels broad application prospects in the field of EMI shielding. Abstract : The microstructures of carbon nanotubes (CNTs)/cellulose composite aerogels are controlled by adjusting the content of tertiary butanol/water co‐solvent and the freezing method. The effect of microstructure on electromagnetic interference shielding performance and mechanism is investigated. Ultimately, composite aerogels with oriented three dimensional fibrous structure presents the most marvelous shielding performance.